Intellectual capacity in women arequipeñas according to their civil status - Delgado Morales, Ronald (2019)
The present project of causal-comparative research focuses on the study of a comparison of the Intelligence Capacity between single women and married women 25 years of age and older in the city of Arequipa. We used a sample of 75 women at least having 31 married and 46 single women, in order to compare the level of intellectual capacity that women from Arequipa have between married and single 25 years old. No causal relationship between the variables was found, assuming the null hypothesis.